Resection of Colorectal Liver Metastases After Second-Line Chemotherapy: Is It Worthwhile? A LiverMetSurvey Analysis of 6415 Patients - Adam, R (2018)
Submitted by Ana Quininha (ana.quininha@chlc.min-saude.pt) on 2018-03-02T15:20:23Z No. of bitstreams: 1 Eur J Cancer 2017 7.pdf: 734043 bytes, checksum: 54e766392f67d2f76df232c0b79eab2a (MD5)